PENGARUH MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS X PADA MATA PELAJARAN BIOLOGI - Handoko, Akbar; Hidayah, Nur; Farhan Barata, Muhammad; Oktafiani, Raicha; Dwi Kesumawardani, Aryani (Universitas Cokroaminoto Palopo, 2024)
This study examines the effect of the Auditory Intellectually Repetition (AIR) model on students' learning motivation and critical thinking skills in Grade X biology at SMA Gajah Mada Bandar Lampung. A quasi-experimental design was used, employing a pre-test post-test control group design. Data collection included critical thinking tests, motivation questionnaires, and documentation. The population comprised all Grade X students, with cluster random sampling selecting X.2 as the experimental group (AIR model) and X.5 as the control group (Direct Instruction model). Hypothesis testing with independent t-tests revealed significant effects of the AIR model, with Sig. (2-tailed) values for learning motivation at 0.001 and critical thinking at 0.000 (both < 0.05). These results confirm that the AIR model significantly enhances learning motivation and critical thinking skills in biology.